Vanuatu : Assessment of the Supervision and Regulation of the Financial Sector Volume I-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2003)
This report assesses Vanuatu's regulatory and supervisory arrangements for the financial sector complied with internationally accepted standards and measures of good practice. It assesses all the main domestic and offshore sectors, as well as the prudential aspects of measures to combat money laundering. It also provides recommended action plans to improve compliance of the Basel Core Principles, cross-sectoral issues, and assessment of the insurance, trust company, and company service provider sectors.